Spirituality and Depression with Self-Moving Trends in Adolescents: Empirical Evidence in Yogyakarta, Indonesia - Sri Setyowati; Suyatno Suyatno (Indonesian Journal of Global Health Research, 2020)
Indonesia is the 14th country with the highest suicide rate in the world and the 8th highest country in ASEAN. Yogyakarta is the city that places the second rank in Indonesia with the highest child and adolescent suicide rates. The purpose of this study is to analyze spirituality and depression with suicidal tendencies in adolescents in Gunungkidul, Yogyakarta. The population in this study were high school and vocational high school students in the Gunungkidul Yogyakarta subdistrict, amounting to 988 students. The number of samples was 301 sampling techniques using purposive sampling. With inclusion criteria: students aged 15-24 years, not being treated in hospital. When the research was conducted in 12 months. Data collection techniques used in this study to capture data about Spirituality Spiritual Involvement and Beliefs Scale (SIBS), depression was measured using the Beck Depression Inventory-II. The method used is of quantitative research using multiple regression. This study found that there is a significant relationship between depression and suicidal tendencies.